Curtain : Poirot's Last Case - Christie, Agatha (London Harpper Collins Publishers, 1993)
A wheelchair-bound Poirot returns to Styles, the venue of his first investigation, where he knows another murder is going to take place...
Keywords: Private investigators -- Country homes -- Murderers